Centriolin, a centriole-appendage protein, regulates peripheral spindle migration and asymmetric division in mouse meiotic oocytes. Issue 19 (2nd October 2017) - Sun, Tian-Yi; Wang, Hai-Yang; Kwon, Jung-Woo; Yuan, Bao; Lee, In-Won; Cui, Xiang-Shun; Kim, Nam-Hyung
ABSTRACT: Unlike somatic cells mitosis, germ cell meiosis consists of 2 consecutive rounds of division that segregate homologous chromosomes and sister chromatids, respectively. The meiotic oocyte is characterized by an absence of centrioles and asymmetric division. Centriolin is a relatively novel centriolar protein that functions in mitotic cell cycle progression and cytokinesis. Here, we explored the function of centriolin in meiosis and showed that it is localized to meiotic spindles and concentrated at the spindle poles and midbody during oocyte meiotic maturation. Unexpectedly, knockdown of centriolin in oocytes with either siRNA or Morpholino micro-injection, did not affect meiotic spindle organization, cell cycle progression, or cytokinesis (as indicated by polar body emission), but led to a failure of peripheral meiotic spindle migration, large polar body emission, and 2-cell like oocytes. These data suggest that, unlike in mitotic cells, the centriolar protein centriolin does not regulate cytokinesis, but plays an important role in regulating asymmetric division of meiotic oocytes.